Transport studies on filler-doped chitosan based polymer electrolyte - Khiar, A.S.A.; Arof, Abdul Kariem; Majid, Siti Rohana; Idris, N.H.; Hassan, M.F.; Winie, T. (Springer Verlag (Germany), 2005)
The room temperature conductivity of the chitosan complex containing 40 wt.% of salt increased from 6.02 x 10(-6) Scm(-1) to 2.10 x 10(-5) Scm(-1) after the addition of 1.0 wt.% aluminosilicate. Conductivity of the electrolyte is contributed from the charge carrier density and ionic mobility. The Rice and Roth model was applied in calculating the mobility, mu and density of ions, n. The number density of ions, n, increases with temperature, while mobility, it decreases with increasing temperature. This work also suggests that the filler did not change the conduction mechanism of the charge carrier in chitosan-salt-filler complexes but helped to increase the conductivity value of the materials.